Mathematical theory of control proceedings of the international conference - Joshi, Mohan C.; Balakrishnan, A.V (Lecture notes in pure and applied mathematics, 1993)
Offers an authoritative overview of the most recent developments in control theory and provides practical examples of effective interaction on topics of common interest to the fields of mathematics and control engineering. Stochastic control and white noise analysis are among the topics discussed.